Effect of Xanthium Strumarium on HIV-1 5′-LTR Transcriptional Activity and Viral Reactivation in Latently Infected Cells - Chen, Chao-Jung; Chiu, Mu-Lin; Hung, Chien-Hui; Liang, Wen-Miin; Ho, Mao-Wang; Lin, Ting-Hsu; Liu, Xiang; Tsang, Hsinyi; Liao, Chiu-Chu; Huang, Shao-Mei; Wu, Yi-Fang; Wu, Yang-Chang; et al. (Frontiers in Pharmacology, 2021)
Chinese herbal medicines (CHMs) are widely used in Asian countries. They show multiple pharmacological activities, including antiviral activities. The 5'-long terminal repeat (LTR) region of HIV-1, required for viral transcription, is a potential drug target for HIV-1 reactivation and intrinsic cell death induction of infected or latently infected cells. Modulation of HIV-1 reactivation requires interactions between host cell proteins and viral 5'-LTR elements. By evaluation of two CHMs- Xanthium strumarium and Pueraria montana, we found that (a) X. strumarium reactivated HIV-1 latently infected cells in J-Lat 8.4, J-Lat 9.2, U1, and ACH-2 cells in vitro; (b) 27 nuclear regulatory proteins were associated with HIV-1 5'-LTR using DNA affinity pull-down and LC-MS/MS analyses; and (c) among them, silencing of XRCC6 reactivated HIV-1 5'-LTR transcriptional activity. We found that X. strumarium inhibits the 5'-LTR associated XRCC6 nuclear regulatory proteins, increases its viral 5'-LTR promoter transcriptional activity, and reactivates HIV-1 latently infected cells in vitro. These findings may contribute to understanding the 5'-LTR activity and the host cell nuclear regulatory protein machinery for reactivating HIV-1 and for future investigations to eradicate and cure HIV-1 infection.